Information technology and the travel industry. - Lau, Dolly Yuin Yuin. (2008)
This project aims to explore the hypothesis that the internet will lead to the demise of travel agents. With the advent of the internet, travel agents who currently serve as middlemen between the customers and travel service providers may become superfluous as potential travellers are able to use the Net for their information needs and travel bookings. Additionally, this research also explores the relationship between Intellectual Capital and the survival of the travel agents.